An Optimal Design of High Output Power CMOS Class E Power Amplifier with Broadband Matching for RFID Applications. Issue 1 (January 2021) - Zahid, Muhammad Noaman; Jiang, Jianliang; Lu, Heng; Khan, Shahrukh; Zhang, Hengli
Abstract: In the radio frequency frontend the power amplifiers are most essential block for reliable wireless communication. Power amplifiers are used for amplification and enhance the input signal to the desired power level at output. The class-E power amplifiers are used in many RF portable electronic devices that need low power consumption, high gain, and high efficiency. In this article, we present an optimum design of a complementary metal-oxide semiconductor (CMOS) class-E power amplifier (PA) that achieves high efficiency and high gain simultaneously for RF based electronic article surveillance (EAS) system. The simulated analysis and implementation of a class-E RF power amplifier with an appropriate output impedance matching network are presented. The proposed CMOS class-E PA has 41.7 dBm output power with 63% of power efficiency at frequency of 7.7 MHz to 8.7MHz.